Formulasi Dan Uji Mutu Fisik Sediaan Sabun Padat Dengan Penambahan Ekstrak Etanol Buah Pepaya (Carica papaya L.) - Putra, Aditya; Sanjiwani, Ni Made Sukma; Suradnyana, I Gede Made; Dewi Agustini, Ni Putu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Papaya fruit contains secondary metabolite compounds such as saponins. The secondary metabolites needed in soap production are saponins. The purpose of this study was to determine whether the addition of ethanol extract of papaya fruit (Carica papaya L.) with concentrations of 2.4 and 6% in solid soap preparations can produce good physical quality and to determine the difference between formula 0 (without extract) and formula I, II and III (with extract concentrations of 2, 4 and 6%) in the physical quality obtained. This research is an experimental study, starting with making extracts formulated into solid soap form with variations in extract concentrations of 2.4 and 6%. The soap produced is white in formula 0 and formula I with an aria fragrance aroma. In contrast, formula II is yellow and formula III is orange with the aroma of papaya fruit ethanol extract and in the four formulas obtained a solid preparation. The homogeneity test results on all formulas are homogeneous. The pH test results obtained the lowest pH value in formula II and formula III with a pH value of 9 while the highest pH value was obtained in formula 0 with a pH value of 11. The test results of the height and stability of the foam obtained the highest foam height in formula III (7.43 cm) with foam stability of 66.82% while the lowest foam height was obtained in formula 0 (6.23 cm) with foam stability of 78.59%. The results of the physical quality test show that the soap meets homogeneous criteria, pH ranges from 9-11, has a foam height of 1.3-22 cm and foam stability between 60-90% in accordance with the requirements of SNI No. 3532-2016.